2021
DOI: 10.1186/s12902-021-00860-0
|View full text |Cite
|
Sign up to set email alerts
|

Variants of the cry 1 gene may influence the effect of fat intake on resting metabolic rate in women with overweight of obesity: a cross-sectional study

Abstract: Background Previous studies have shown that the minor allele (C allele) for Cry 1 rs2287161, may be associated with increased risk of cardiovascular diseases (CVDs). Low resting metabolic rate (RMR) caused by the diet has been shown to have, potentially, unfavorable effects on obesity. This study sought to investigate the interactions between the Cry 1 Gene and fat intake on RMR in women with overweight of obesity. Methods This comparative cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…Also, in the total population, higher whole grain intake was associated with an increased level of HDL-C. The findings of the present study are comparable with the results of several previous studies that investigated the possible association of HEI with CVD risk factors and metabolic abnormalities risk (Ziaee et al, 2021;Shah et al, 2010;Saraf-Bank et al, 2017;Monfort-Pires et al, 2014;Huffman et al, 2011;Daneshzad et al, 2019;Asghari et al, 2012a;Zeinalabedini et al, 2023;Firouzabadi et al, 2023;Ahmadijoo et al, 2023); these previous studies have reported the controversial findings on the possible relationship between HEI and the risk of cardiometabolic disorders. Contrary to our results, some studies supported the beneficial role of a diet with a high HEI score in reducing the risk of metabolic disorders; however, similar to our study, some studies did not observe significant results.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Also, in the total population, higher whole grain intake was associated with an increased level of HDL-C. The findings of the present study are comparable with the results of several previous studies that investigated the possible association of HEI with CVD risk factors and metabolic abnormalities risk (Ziaee et al, 2021;Shah et al, 2010;Saraf-Bank et al, 2017;Monfort-Pires et al, 2014;Huffman et al, 2011;Daneshzad et al, 2019;Asghari et al, 2012a;Zeinalabedini et al, 2023;Firouzabadi et al, 2023;Ahmadijoo et al, 2023); these previous studies have reported the controversial findings on the possible relationship between HEI and the risk of cardiometabolic disorders. Contrary to our results, some studies supported the beneficial role of a diet with a high HEI score in reducing the risk of metabolic disorders; however, similar to our study, some studies did not observe significant results.…”
Section: Discussionsupporting
confidence: 88%
“…, 2023). Another cross-sectional study conducted on 377 Iranian obese women showed that adherence to a diet with a higher score of HEI may decrease the odds of elevated LDL-C, hypertension and hyperglycemia (Firouzabadi et al. , 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted on Cry1 polymorphism demonstrated that SFA intake was significantly lower in the non-risk allele genotype group compared to the group with risk allele present. 61 In this study, subjects in the third tertile of LCD consumed higher amounts of some elements which are necessary for insulin modulation such as calcium and zinc. One of the possible reasons for the interaction of LCD and Cry1 on insulin resistance and insulin sensitivity might be the intake or level of minerals.…”
Section: Low Adherence High Adherencementioning
confidence: 74%
“…Normality distribution was analyzed by Kolmogorov–Smirnov’s test (p > 0.05). The Hardy-Weinberg Equilibrium and comparison of categorical variables were assessed with the χ 2 test [ 28 ]. Quantitative variables were reported as the means and SD and categorical characteristics information were reported as numbers and percentages.…”
Section: Methodsmentioning
confidence: 99%